HIKAYAT TABUT (Suatu Tinjauan Filologi dan Sintaksis) - Afrita, Eni (Humanus, 2012)
Codex as heritage, full of life values, is only useful once it is researched, particularly philologically. The tradition of text duplicating of the codices that only relied on intuitive or diplomatic method will practically help the reader the least.In general this research aims to give opportunity to broader society to recognize, study, and enjoy ancient writing. On the other hand, the target particularly is to reveal the digression of spelling and text characteristic, and the supposed form of the Tabut Saga text edition.Key words: evaluation philology and sintacsys, saga of tabut